Greening industries and creating jobs (Brussels, 2012)
"How the objective of a resource-efficient low carbon economy is to be reached and how the transition is managed are the key issues addressed by this publication. The two main focuses are industrial policy and employment prospects on the road to a green economy that retains its industrial base. Any lasting recovery of the real economy will necessarily take the shape of a more resource-efficient production model. While we argue that only a more ambitious and comprehensive European climate policy framework would have a chance of delivering the broader 2050 climate targets, this does not mean that Europe has to give up its industrial base and its related competences. Several chapters of this book argue that the option of attaining a low-carbon economy through ‘deindustrialisation’ would prevent Europe from preserving its competitiveness and knowledge base, which are also essential for exploiting the potential of the emerging eco-industry. While decoupling economic growth from resource use is also possible with an industrial base that is more energy-and resource-efficient, this does require a fundamental shift in terms of how the economy is managed and how business decisions are made. Sustainable industrial and structural policies are needed also in order to ensure that this revolutionary process takes place in a socially balanced manner."